Activity of antibodies against Salmonella dublin, Toxoplasma gondii, or Actinobacillus pleuropneumoniae in sera after treatment with electron beam irradiation or binary ethylenimine. - Kyvsgaard, N C (1996)
Viral contamination of biological material may constitute a risk when samples are exchanged between countries, and it may be necessary to subject the material to an inactivation treatment. The present study investigated possible adverse effects on antibody activity subsequent to either electron beam irradiation or binary ethylenimine (BEI) treatment. The treatments were performed with sera obtained from pigs or cattle. For each treatment level, the posttreatment activity was plotted against the pretreatment activity, and regression analyses were carried out. The slope of the regression line was used as an estimate for the relative posttreatment activity. For a Toxoplasma gondii indirect enzyme-linked immunosorbent assay (ELISA) and agglutination assay as well as for a Salmonella dublin indirect ELISA, the posttreatment activity was more than 89% of the pretreatment activity when the samples were irradiated in the frozen state (on dry ice) with up to 46. kGy or when they were treated with 5 or 10 mM BEI for up to 48 h. The samples were more sensitive to irradiation in the liquid state. Thus, samples irradiated with 22.6 kGy retained 98% of their activity in the indirect ELISA when they were irradiated in the frozen state on dry ice but only 35% of their activity when they were irradiated in the liquid state at 0 degrees C. The patterns seen in an S. dublin blocking ELISA and an Actinobacillus pleuropneumoniae complement fixation assay differed in that samples with a low level of pretreatment activity were subject to a relatively greater decrease in activity than samples with a high level of pretreatment activity. The complement fixation assay was particularly sensitive to irradiation of serum. It is concluded that serum samples retain sufficient activity by both methods of virus inactivation, especially when used in indirect ELISA or in the T. gondii agglutination assay.